The Influence of Chronic Ego Depletion on Goal Adherence: An Experience Sampling Study - Wang, Ligang (PLoS One, 2015)
Although ego depletion effects have been widely observed in experiments in which participants perform consecutive self-control tasks, the process of ego depletion remains poorly understood. Using the strength model of self-control, we hypothesized that chronic ego depletion adversely affects goal adherence and that mental effort and motivation are involved in the process of ego depletion. In this study, 203 students reported their daily performance, mental effort, and motivation with respect to goal directed behavior across a 3-week time period. People with high levels of chronic ego depletion were less successful in goal adherence than those with less chronic ego depletion. Although daily effort devoted to goal adherence increased with chronic ego depletion, motivation to adhere to goals was not affected. Participants with high levels of chronic ego depletion showed a stronger positive association between mental effort and performance, but chronic ego depletion did not play a regulatory role in the effect of motivation on performance. Chronic ego depletion increased the likelihood of behavior regulation failure, suggesting that it is difficult for people in an ego-depletion state to adhere to goals. We integrate our results with the findings of previous studies and discuss possible theoretical implications.